2012
DOI: 10.1088/0953-4075/45/21/215206
|View full text |Cite
|
Sign up to set email alerts
|

Positron scattering from O2

Abstract: We report on recent cross section results for positron scattering from molecular oxygen (O2). Total cross sections (TCSs) were measured with a positron spectrometer in the energy range from 0.1 to 50 eV and with an energy resolution of the positron beam of ∼0.25 eV. In addition, TCSs as well as elastic and inelastic integral cross sections were computed within the independent atom model and screening corrected additivity rule approach, with both dipole and dipole plus quadrupole polarization potentials, betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
73
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 56 publications
14
73
4
Order By: Relevance
“…57 In those studies, reasonable agreement was found with the reported experimental results. In addition, we have also investigated the molecular systems NO 2 , N 2 O, 3-hydroxy-tetrahydrofuran, 58 and pyrimidine with our IAM-SCAR approach, and while the results from those studies are waiting to be written up for publication they are generally found to be in quite reasonable agreement with the available TCS data.…”
Section: B Atomic Optical Model For Positron Scatteringsupporting
confidence: 84%
“…57 In those studies, reasonable agreement was found with the reported experimental results. In addition, we have also investigated the molecular systems NO 2 , N 2 O, 3-hydroxy-tetrahydrofuran, 58 and pyrimidine with our IAM-SCAR approach, and while the results from those studies are waiting to be written up for publication they are generally found to be in quite reasonable agreement with the available TCS data.…”
Section: B Atomic Optical Model For Positron Scatteringsupporting
confidence: 84%
“…More recently, the IAM-SCAR method has also been successfully applied to positron scattering studies from argon, 35 diatomics such as molecular oxygen, 36 and to macro-molecules, such as THF, 9 where fair agreement was typically found with the reported measurements. As the details of our theory have already been presented in those papers, here we only briefly summarize the method behind our calculations.…”
Section: Theory Detailsmentioning
confidence: 99%
“…(1) represents the elastic scattering process and consists of the electrostatic interaction term, V s (r), and the polarization term, V p (r), whereas the imaginary part accounts for inelastic processes which are considered as absorptions, V a (r), from the incident positron beam. The details of our static, polarization and absorption potentials have recently been described by Chiari et al 36 and therefore are not revisited here. Nevertheless, it is worthwhile to stress that, unlike with electrons, for positron collisions the definition of the energy for the absorption threshold ( ) is somewhat controversial.…”
Section: A Atomic Optical Modelmentioning
confidence: 99%
“…However studies regarding positron scattering are scarcer and the majority of them have been restricted to a limited energy domain, either at low [6] or high energies [7]. Moreover, the computational analysis of positron scattering with polyatomic molecules is still fairly limited to relatively simple molecular structures [7][8][9]. In order to extend our knowledge of radiationinduced damage in biomolecular systems and provide relevant parameters for radiation-based biomedical applications, it is necessary to apply these models to increasingly more complicated biomolecules.…”
Section: Introductionmentioning
confidence: 99%